Adverse childhood experiences, posttraumatic stress, and FKBP5 methylation patterns in postpartum women and their newborn infants. (April 2020) - Grasso, Damion J.; Drury, Stacy; Briggs-Gowan, Margaret; Johnson, Amy; Ford, Julian; Lapidus, Garry; Scranton, Victoria; Abreu, Christine; Covault, Jonathan
Highlights: Genetic variation and epigenetic processes involving FKBP5 have been implicated in trauma-related impairment in adults. Evidence suggests FKBP5 may be implicated in the intergenerational transmission of trauma-related effects in adult offspring. The current study examined epigenetic processes involving FKBP5 and intergenerational effects of maternal adversity/trauma. Results reflected allele-specific associations between FKBP5 methylation and maternal childhood adversity and PTSD symptoms. Findings provide mechanistic insight into the intergenerational impact of maternal childhood adversity and PTSD in pregnancy. Abstract: Background: Genetic variation and epigenetic mechanisms involving the stress-related gene FKBP5 have been implicated in the intergenerational transmission of trauma-related effects in adult offspring of trauma-exposed caregivers, but these processes have not been fully explored in postpartum women and their newborn infants. Methods: Women recruited from a prenatal care clinic during their third trimester of pregnancy ( N = 114) completed a battery of instruments assessing adverse childhood experiences (ACEs), adversity in adulthood, posttraumatic stress disorder (PTSD) symptoms, negative emotional state, and emotion dysregulation. FKBP5 rs1360780 genotype and intron 7 methylation were derived from saliva collected from postpartum mothers and their newborn infants within 24 h of delivery. Results: Allele-specific associations of methylation with maternal ACEs and prenatal trauma-related symptoms were evident; however, relations differed between mothers and newborns. In mothers carrying the stress sensitive T-allele (CT and TT genotypes), maternal FKBP5 methylation negatively correlated with threat-based ACEs and maternal PTSD symptoms during pregnancy, but not deprivation-based ACEs. In infants homozygous for the C allele (CC genotype), infant FKBP5 methylation positively correlated with maternal threat-based ACEs and prenatal PTSD symptom severity, but not deprivation-based ACEs or adversity in adulthood. Conclusions: Our results provide evidence that links maternal threat-based ACEs and trauma-related symptoms during pregnancy with allele-specific epigenetic patterns in postpartum women and their newborn infants. These findings provide mechanistic insight into the potential intergenerational impact of ACEs and the effect of maternal PTSD symptoms during pregnancy.